If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 + 9x + 8 = 0 Reorder the terms: -1 + 8 + 6x + 9x = 0 Combine like terms: -1 + 8 = 7 7 + 6x + 9x = 0 Combine like terms: 6x + 9x = 15x 7 + 15x = 0 Solving 7 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 15x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 15x = 0 + -7 15x = 0 + -7 Combine like terms: 0 + -7 = -7 15x = -7 Divide each side by '15'. x = -0.4666666667 Simplifying x = -0.4666666667
| (3x)(49)=(14x) | | -3(2t+3)=-33 | | 85f=685 | | 5v+x=w^2 | | 15p-5p+4=9 | | -10(s+1)=51 | | 0.72*c=7.5 | | 5x-3+2x=7x+7 | | 48/-16= | | 5x-1=231 | | 3+2(5x+6)=5 | | 5(4s+6)=130 | | h-10=27 | | 8x-19=4-7x | | -1470=-5x-210 | | 8(2l+7)=72 | | -(3+6)+2x=-(6+2)-3.3 | | 14z=18+12z | | -30-29= | | 5x+7=6z | | 12[x]1/3 | | 2y-3=5-s | | 14z=18+12m | | x^2+ab-ax-bx=0 | | 0=-5x-210 | | 2x+1=52 | | (u-8)*10=20 | | 2(-13)=4(16-u) | | 7+h=23 | | 8-c=(-12)-3c | | 4(x-2)+2=14 | | z-2=35 |